Los derechos monetarios y la gestión financiera oportuna en el GAD municipal Riobamba durante el periodo 2022. - Naranjo Ramírez, Angel Raúl (Machala : Universidad Técnica de Machala, 2023)
Since the end of the government of Lenin Moreno and the beginning of the current government, Ecuador has been committed to fiscaldiscipline and macroeconomic stability, in order to avoid an unsustainable increase in debt and by specifying the monetary policies that have been established by the state, towards decentralized autonomous governments. From these premises, the research is proposed, with the aim of analyzing monetary rights and their impact on the financial management of the Riobamba municipal GAD during the year 2022. The scientific study merited the application of the methodology to direct the project, framed under a post-positivist and constructivist paradigm, correlational, with a mixed approach, of non-experimental design, through the deductive, inductive and empirical method. Concluding that there is a correlation between the variables analyzed, therefore, the legal provisions related to monetary rights and timely financial management are elements that have not been correctly applied in the mu nicipal GAD of Riobamba.
Desde finales del gobierno de Lenin Moreno y comienzos del actual gobierno, el Ecuador se ha visto comprometido con la disciplina fiscal y la estabilidad macroeconómica, a fin de evitar un aumento insostenible de la deuda y precisando las políticas monetarias que han sido establecidas por el estado, hacia los gobiernos autónomos descentralizados. Desde estas premisas, se plantea la investigación, con el objetivo de analizar los derechos monetarios y su incidencia en la gestión financiera del GAD municipal Riobamba durante el año 2022. El estudio científico ameritó la aplicación de la metodología para direccionar el proyecto, enmarcado bajo un paradigma post-positivista y constructivista, de tipo correlacional, con un enfoque mixto, de diseño no experimental, mediante el método deductivo, inductivo y empírico. Concluyendo que existe una correlación entre las variables analizadas, por tanto, las disposiciones legales relacionadas con los derechos monetarios y la gestión financiera oportuna son elementos que no se han aplicado correctamente en el GAD municipal del Riobamba.
Keywords: DERECHO MONETARIO; GESTIÓN FINANCIERA; GOBIERNO AUTÓNOMO DESCENTRALIZADO; PRESUPUESTO